Range-separated hybrid functionals in full-potential LAPW using adaptively compressed exchange - Jānis Užulis; Aleksandr V. Sorokin; Andris Gulans (npj Computational Materials)
Abstract The adaptively compressed exchange (ACE) operator is a low-rank representation of the Fock exchange, avoiding any loss of precision. We present an application of this method in the formalism of linearized augmented plane waves (LAPW) to hybrid functionals with range separation. For this purpose, we extend the functionality of the LAPW-specific Poisson solver employing the pseudocharge method for the short- and long-range interaction kernels. To make these calculations more affordable, we revise the most expensive steps in the pseudocharge method and reduce their computational complexity. As a result, this implementation is a first step towards cubic-scaling hybrid calculations employing LAPW with respect to the number of atoms. We apply our code for assessing the numerical quality of band gaps computed with hybrid functionals in the literature, employing a test set consisting of 26 materials.